P–500 Euploid embryo-transfer reduces advanced maternal age patients' anxiety in the waiting period before the pregnancy-test. (6th August 2021) - Forte, M; Faustini, F; Venturella, R; Rania, E; Alviggi, E; Trabucco, E; Cimadomo, D; Capalbo, A; Zullo, F; Ubaldi, F; Rienzi, L
Abstract: Study question: Can PGT-A reduce the anxiety generally experienced by infertile women undergoing IVF in the waiting period between embryo transfer and the pregnancy test? Summary answer: PGT-A reduces anxiety in infertile women after embryo transfer, probably due to a gain of confidence in their treatment route. What is known already: The waiting period, i.e. the time between embryo-transfer and the pregnancy-test, is considered unpredictable and unmanageable, thus figuring amongst the most stressful steps of an IVF treatment. This is mainly imputable to women's lost sense of control over the outcome. Uncertainty is in fact a source of fear and elevated distress. PGT-A has been shown to improve live birth rate per embryo transfer and reduce miscarriage rate per clinical pregnancy across several trials and observational studies worldwide, especially in advanced maternal age (AMA) women. Here, we investigated if euploid embryo transfer does involve also lower emotional burden over untested one. Study design, size, duration: Prospective observational study evaluating the level of anxiety in the waiting period among women undergoing euploid or untested embryo transfer. Data were collected between September 2019 and September 2020 in a public hospital. A total of 48 infertile women were recruited: 25 undergoing euploid single embryo transfer after trophectoderm biopsy and NGS, and 23 undergoing untested single embryo transfer. Participants/materials, setting, methods: To measure the level of anxiety, the two groups completed the STAI (State Trait Anxiety Inventory) questionnaire at two time points: before starting the ovarian stimulation (T0), and at day 8 after embryo transfer (T1). The chosen questionnaire has been previously validated to capture the level of patients' anxiety during the waiting period. Outcomes of T0 were used to control for individual level state of anxiety at T1. Main results and the role of chance: The two groups showed similar reproductive history and sociodemographic characteristics except for female age, which was higher in the PGT-A group (37.7±3.2 yr versus 32.3±2.2 yr in the control). This is due to AMA (maternal age >35 yr) being the main indication to PGT-A. Conversely, the duration of infertility was similar in the two groups (3.8±2.2 yr versus 3.7±1.9 in the control). At T0 all patients showed similar levels of anxiety (46.4 points versus 49.9 in the control, 95%CI of the difference: from –9.97 to 3.03 points, p = 0.3). Remarkably, at T1 instead, the women undergoing euploid embryo transfer showed a significantly decreased level of anxiety with respect to the control (39.9 points versus 53.4; 95% CI of the difference: from –18.26 to –8.69, p < 0.01). This difference remained significant also after controlling for the baseline value at T0, and adjusting for potential confounding factors in a multivariate analysis (adjusted p-value<0.01). Limitations, reasons for caution: The sample size is small, yet the study resulted powered enough to reveal the considerable advantage of PGT-A toward the primary outcome. We analysed only the waiting period here. Therefore, data will be collected in the future at subsequent gestational stages, such as when prenatal genetic diagnosis is usually conducted. Wider implications of the findings: Women undergoing PGT-A seem reassured by the technique. This is probably due to the gain of confidence and control derived from an increased expectation of success. From this perspective, assessing women's wellbeing and attitude towards all different clinical procedures should become a critical part of their treatment. Trial registration number: None